Between secularization and reform: religion in the enlightenment - Tomaszewska, Anna (Brill's studies in intellectual history, 2022)
The authors revisit the idea that Enlightenment spearheaded secularization. This book invites all to look at the Enlightenment religiosity as founded on a merger of religious criticism and heterodoxy